Review essay: Politics and entertainment: A happy marriage? - van Santen, Rosa (Javnost-The Public, 2008)
Reviewed books: - Arnsfeld, Andreas. 2005. Medien – Politik– Gesellschaft: Aspekte ihrer Wechselwirkungen unter dem Stichwort Politainment. Marburg: Tectum Verlag. - Jones, Jeffrey P. 2005. Entertaining Politics: New Political Television and Civic Culture. Lanham: Rowman & Littlefield. - Nieland, Jörg-Uwe and Klaus Kamps, eds. 2004. Politikdarstellung und Unterhaltungskultur: Zum Wandel der politischen Kommunikation. Köln: Herbert von Halem Verlag. - Thussu, Daya Kishan. 2007. News as Entertainment: The Rise of Global Infotainment. London: Sage. - Van Zoonen, Liesbet. 2005. Entertaining the Citizen: When Politics and Popular Culture Converge.Lanham: Rowman & Littlefield.